Validity of beveridge curve: Türkiye application with non-linear cointegration analysis - Kubar, Yesim; Ketenci, Seyit Taha; Yilmaz, Ikranur (Peter Lang AG, 2025)
[Abstract Not Available]
Keywords: Cointegration analysis; Non linear; Bulk Density